Boarfish protein recovery using the pH-shift process and generation of protein hydrolysates with ACE-I and antihypertensive bioactivities in spontaneously hypertensive rats. (October 2016) - Hayes, Maria; Mora, Leticia; Hussey, Karen; Aluko, Rotimi E.
Abstract: Boarfish ( Capros aper Linnaeus) are frequently in European waters. In this work, the generation and identification of angiotensin-I-converting enzyme (ACE-I; EC 3.4.15.1) inhibitory and antihypertensive peptides from Boarfish proteins are reported for the first time. Boarfish proteins were recovered using the pH shift process and hydrolysates were generated using the commercially available proteolytic enzyme alcalase CLEA, papain and protease AP. Molecular weight cut off (MWCO) filtration methods were used to enrich for peptides less than 10- and 3-kDa in size. The angiotensin-I-converting enzyme (ACE-I; EC 3.4.15.1) inhibitory activity of the generated hydrolysates and MWCO fractions was assessed in vitro . The 3-kDa Boarfish protein hydrolysate (BPH) generated using protease AP inhibited ACE-I by 85.8% (± 1.81) when assayed at a concentration of 1 mg/mL compared to the positive control captopril. Mass spectrometry was used to characterize the peptides within the BPH generated using protease AP. Moreover, the antihypertensive activity of this BPH was assessed in vivo using spontaneously hypertensive rats (SHRs) over a 24 hour period. Results obtained suggest that BPH generated using protease AP is a source of ACE-I-inhibitory peptides with antihypertensive effects in vivo . This hydrolysate has the potential for use as a functional food ingredient for the maintenance of normal blood pressure in hypertensive individuals. Industrial relevance: This paper provides a potential alternative for marine processors for utilisation of their total catch in the generation of functional foods. Discarded fish represents an obstacle to the sustainability of global fisheries. Due to the fact that the reformed European Common Fisheries Policy promotes landing of all species under the Total Allowable Catch (TACs) policy in Europe, it will be necessary for processors to utilise all species caught to prevent disposal costs. Boarfish are caught presently as a co-product with other fish. In light of the new regulation and costs for disposal at landfill it will therefore be necessary to convert Boarfish into value added products. Industry in Ireland and Denmark are particularly interested in this topic as have the largest quota for Boarfish within the EU. This paper describes a methodology for generation of protein hydrolysates from Boarfish with added health benefits. This area is of increasing, commercial interest to marine processors and food product developers as fish are a known source of bioactive peptides. Boarfish ( Capros aper Linn) are frequently discarded in European waters. In this work, the generation and identification of angiotensin-I-converting enzyme (ACE-I; EC 3.4.15.1) inhibitory and antihypertensive peptides from Boarfish proteins is reported for the first time. Boarfish proteins were recovered using the pH shift process and hydrolysates were generated using the commercially available proteolytic enzymes alcalase CLEA, papain and protease AP. Molecular weight cut off (MWCO) filtration methods were used to enrich for peptides less than 10- and 3-kDa in size. Highlights: Characterization of boarfish peptides generated using the pH shift process for the first time Generation of Boarfish hydrolysates using commercially available enzymes Identification of an ACE-I inhibitory activities in vitro Identification of an antihypertensive effect in vivo in spontaneously hypertensive rats Provides a potential alternative use for Boarfish than fish/animal feed